Efecto del desmane y aplicación de fitorreguladores sobre el tamaño y calidad post-cosecha de frutos del plátano cv. Dominico (musa aab simmonds) - Mendoza Macías, Josselyn Stephanie (2019)
Desmane (elimination of hands) and application of phytoregulators directed to the bunch, is a practice that is used to improve the quality of the bunch. The research was carried out at Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López, in the dry season from June to December with the objective of evaluating the effect of desmanent (elimination of hands) and application of phytoregulators on size and quality post-harvest of banana fruits cv. Dominican. The plant material used was banana cv. Dominican of a year and a half old plantation. The completely randomized design (DCA) was used in factorial arrangement A x B + 1 with 16 treatments and three repetitions, with a total of 48 experimental units. The experimental unit consisted of three banana plants cv. Dominican desmanent (hand pruning) significantly influenced the increase in the size of the Dominican banana fruits, so this characteristic could be used for export purposes. The phytoregulators based on cytokinins increased the green time on the hanger of banana fruits, so this technology could be suggested for fruits intended for marketing in supermarkets in order to reduce post-harvest losses.